2021
DOI: 10.1101/2021.07.02.450904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An fMRI meta-analysis of the role of the striatum in everyday-life vs laboratory-developed habits

Abstract: The dorsolateral striatum plays a major role in stimulus-response habits that are learned in the experimental laboratory. Here, we use meta-analytic procedures to identify the neural circuits activated during the execution of stimulus-response behaviours acquired in everyday-life and those activated by habits acquired in the laboratory. In the case of everyday-life habits we dissociated motor and associative components. We found that motor-dominant stimulus-response associations developed outside the laborator… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 229 publications
2
1
0
Order By: Relevance
“…One potential mechanism could be an increase in inhibitory control over habit-driven behavior. This interpretation is consistent with findings that this region of the striatum has frequently been implicated in inhibitory control as well as habit learning and execution [69][70][71][72]. For example, a recent metaanalysis found that neural representations of both laboratory-produced habits and naturalistic habits acquired outside the laboratory are localized in the caudal putamen [70].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One potential mechanism could be an increase in inhibitory control over habit-driven behavior. This interpretation is consistent with findings that this region of the striatum has frequently been implicated in inhibitory control as well as habit learning and execution [69][70][71][72]. For example, a recent metaanalysis found that neural representations of both laboratory-produced habits and naturalistic habits acquired outside the laboratory are localized in the caudal putamen [70].…”
Section: Discussionsupporting
confidence: 88%
“…This interpretation is consistent with findings that this region of the striatum has frequently been implicated in inhibitory control as well as habit learning and execution[69-72]. For example, a recent meta-analysis found that neural representations of both laboratory-produced habits and naturalistic habits acquired outside the laboratory are localized in the caudal putamen[70]. Misconfiguration of this component of the habit execution circuit during acute abstinence may serve to reduce the propensity for habit-driven smoking behavior despite negative withdrawal symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…Empirical validation that sequential tasks rely on habit learning comes from recent meta-analyses of neural activation studies (Guida et al, 2022;Patterson & Knowton, 2018). The habit-related sensorimotor network, especially the posterior dorsal putamen, supplementary motor area, and cerebellum, became activated when participants had extensively practiced motor-sequence-learning tasks.…”
Section: How Habits Guide Respondingmentioning
confidence: 99%